Contributions of Public Investment to Economic Growth and Productivity - Sungmin Han (KDI Journal of Economic Policy, 2017)
Whereas a large variety of previous studies show mixed results regarding the relationship between public investment and economic outcome, several studies have been conducted on related issues in Korea. The present study deals with the effect of public investment in Korea on economic growth and productivity. Using administrative data, it exploits three different methodologies: the total factor productivity approach, production function approach, and stochastic frontier production function approach. The results of this study show that public investment has a statistically significant effect on economic growth. However, it contributes little to enhance productivity. It is explained that there exists inefficiency of production in the Korean economy. These findings indicate that public investment has played a central role in the direct input factor and not in indirect role in Korea. Thus, it is necessary for public investment policies to concentrate on enhancing the efficiency of the Korean economy.
Keywords: C13; D24; H41; 330; Public Investment; Public Capital; Total Factor Productivity; Production Function; Stochastic Frontier Production Function